A Treasure of Bioactive Compounds from the Deep Sea - Assunta Saide; Chiara Lauritano; Adrianna Ianora (Biomedicines, 2021)
The deep-sea environment is a unique, challenging extreme habitat where species have had to adapt to the absence of light, low levels of oxygen, high pressure and little food. In order to survive such harsh conditions, these organisms have evolved different biochemical and physiological features that often have no other equivalent in terrestrial habitats. Recent analyses have highlighted how the deep sea is one of the most diverse and species-rich habitats on the planet but less explored compared to more accessible sites. Because of their adaptation to this extreme environment, deep-sea species have the potential to produce novel secondary metabolites with potent biological activities. Recent advances in sampling and novel techniques in microorganism culturing and chemical isolation have promoted the discovery of bioactive agents from deep-sea organisms. However, reports of natural products derived from deep-sea species are still scarce, probably because of the difficulty in accessing deep-sea samples, sampling costs and the difficulty in culturing deep-sea organisms. In this review, we give an overview of the potential treasure represented by metabolites produced by deep marine species and their bioactivities for the treatment and prevention of various human pathologies.